Exploring the Interlinkages Between Gender, Power, and Health in the Entertainment Establishment Settings in Kathmandu Nepal. (July 2020) - Basnyat, Iccha
This article explores the ways in which gender inequalities are reproduced and reinforced within entertainment establishments, and in turn the ways in which it affects health of the women working in these establishments. Specifically, this article is based on 35 in-depth interviews with women working in entertainment establishments in Kathmandu, Nepal. The findings highlight daily encounters of harassment by customers demanding engagement and acceptance of various sexual advances; strategies of exploitation by employers such as threatening the loss of work and/or salary to coerce the women into engaging in sexual talks and innuendoes to increase sales for the business; and an adverse impact on the physical, emotional, and psychological health of women working in the entertainment establishment. The findings urge us to locate the discussion of health, particularly health of marginalized women, within the context of gender inequalities, labor divisions, and power relations.